The Impact of Work Motivation, Job Stress, and Organizational Commitment on Employees' Intentions to Depart from Lombok Idjo Restaurant in Yogyakarta - Gurito, Anang; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of work motivation, work stress and organizational commitment on employee turnover intention at Lombok Idjo Restaurant Yogyakarta. The findings from the Instrument Test indicate that the data gathered in this study are both valid and reliable. Furthermore, the Classical Assumption Test confirms that the data are normally distributed and that the regression model developed is devoid of multicollinearity, heteroscedasticity, and autocorrelation. The results of this study prove that: (1) Work motivation has no significant effect on employee turnover intention at Lombok Idjo Restaurant Yogyakarta. (2) Job stress has a positive and significant effect on employee turnover intention of Lombok Idjo Yogyakarta Restaurant, and (3) Organizational commitment does not have a substantial impact on the intention of employees at Lombok Idjo Yogyakarta Restaurant to leave the organization..